The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1975
DOI: 10.1093/jaoac/58.1.117
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Official Fluorometric Method for Selenium in Plants

Abstract: The official first action AOAC fluorometric method for selenium in plants, 3.074–3.078, has been modified to simplify the method and to make it more accurate. The digestion time has been increased from 15 to 30 min past the appearance of perchloric acid fumes to better assure complete oxidation of all forms of selenium to selenite. Preparation of the 2,3-diaminonaphthalene solution, the reagent used for fluorometric analysis, has been changed so that the reagent is stable for several weeks; in the previous wri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0
10

Year Published

1998
1998
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(78 citation statements)
references
References 0 publications
0
68
0
10
Order By: Relevance
“…The solution was centrifuged at 15,000 g for 1 h, and the red elemental Se was pelleted. Se level in the supernatant was below detection limit (< 0.05 µg/ml) using a fluorescent assay [26], and the BSA content in supernatant was found unchanged. These data suggested that the purity of Nano-Se was 99.9875% and Se in BSA-bound form was less than 0.0125%.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The solution was centrifuged at 15,000 g for 1 h, and the red elemental Se was pelleted. Se level in the supernatant was below detection limit (< 0.05 µg/ml) using a fluorescent assay [26], and the BSA content in supernatant was found unchanged. These data suggested that the purity of Nano-Se was 99.9875% and Se in BSA-bound form was less than 0.0125%.…”
Section: Discussionmentioning
confidence: 86%
“…It can be assumed that the final preparation will likely contain 1/ BSA bound Se in the form of Cys-S-Se-to cysteine residue 34. To investigate this possibility, Nano-Se was dissolved in water, Se and BSA content in solution was 401.4 ± 2.2 µg/ml [26] and 4.03 ± 0.11 mg/ml [6] respectively. The solution was centrifuged at 15,000 g for 1 h, and the red elemental Se was pelleted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selenium content was determined according to the method described by Olson et al (1975). Copper and zinc were analysed using the methods 985.…”
Section: Mineralsmentioning
confidence: 99%
“…Density (g/cm3at 258C) was determined by gently pouring the brazil nut powder into a 10 cm3 graduated cylinder and was calculated as the ratio of the weight (g) of the sample contained in the cilinder to the volume occupied (i.e., 10 cm3) (Gallo, Llabot, Allemandi, Bucata, & Pinna, 2011). The Se content was set according to Olson, Palmer, and Cary (1975).…”
Section: Physicochemical Features Of the Productmentioning
confidence: 99%